Nanoparticle-Mediated Delivery of Emodin via Colonic Irrigation Attenuates Renal Injury in 5/6 Nephrectomized Rats - Lu, Zhaoyu; Ji, Chunlan; Luo, Xuewen; Lan, Yong; Han, Lijuan; Chen, Yang; Liu, Xusheng; Lin, Qinzhan; Lu, Fuhua; Wu, Xiuqing; Guo, Rui; Zou, Chuan (Frontiers in Pharmacology, 2021)
Our previous study has shown that emodincolonic irrigation modulates gut microbiota and delays CKD progression. However, the poor solubility, limited of colonic irrigation retention time and inadequate colon adhesion of emodin hindered its clinical application. According to the deficiency of emodin, we prepared the monomethoxy-poly (ethylene glycol)-poly (lactic acid)-chitosan- 2-mercaptobenzimidazole(mPEG-PLA-CS-MBI) nanoparticle incorporating emodin (emodin-NP) and study its efficacy in delays CKD progression. Male Sprague-Dawley rats underwent surgical removal of 5/6 of nephrectomy. Emodin-NP was administered via colonic irrigation every two daysfor eight weeks. We found that treatment with emodin-NP improved kidney function, limited expansion of tubulointerstitial fibrosis. Treatment of emodin-NP once every two days is comparable to emodin treatment once a day. Furthermore, emodin-NP via colonic irrigation remarkably reduced serum IL-1β，IL-6 and LPSlevels,improve intestinal barrier function and down-regulates intestinal TLR4, MyD88 and NF-κb levels.16SrDNA analyses showed that emodin-NP could regulate microbiota disturbance in CKD.Taken together, these results suggest that Emodin-NP alleviated kidney dysfunction and tubulointerstitial fibrosis and, mediated through modification of gut microbiota disorders. Maybe Emodin-NP is a new method to treat CKD.